Stereo and Shading Contribute Independently to Shape Convexity-Concavity Discrimination. (April 2014) - Aubin, Mercédès; Arguin, Martin
The present study examined the joint contribution of shading and stereopsis to the perception of shape convexity–concavity. The stimuli were the images of a synthetic convex 3-D shape seen from viewpoints leading to ambiguity as to its convexity. Illumination came from either above or below, and from either the right or the left, and stimuli were presented dichoptically with normal binocular disparity, reversed disparity, or no disparity. Participants responded "convex" more often when the lighting came from above than from below. Also, participants responded that the shape was convex more often with normal than with zero disparity, and more often with zero disparity than with reversed stereopsis. The effects of lighting direction and display mode were additive—that is, they did not interact. This indicates that shading and stereopsis contribute independently to shape perception.